Identification and characterization of six peroxiredoxin transcripts from mud crab Scylla paramamosain: The first evidence of peroxiredoxin gene family in crustacean and their expression profiles under biotic and abiotic stresses. (January 2018) - Tu, Dan-Dan; Zhou, Yi-Lian; Gu, Wen-Bin; Zhu, Qi-Hui; Xu, Bin-Peng; Zhou, Zhong-Kai; Liu, Ze-Peng; Wang, Cong; Chen, Yu-Yin; Shu, Miao-An
Highlights: Prx gene family was firstly identified from the mud crab. The expression profiles of SpPrx s under biotic and abiotic stresses were investigated. The comparative analysis of Prx family in invertebrates and vertebrates was conducted for the first time. The peroxidase activity of Sp Prxs was firstly determined. Abstracts: The peroxiredoxins (Prxs) define a novel and evolutionarily conserved superfamily of peroxidases able to protect cells from oxidative damage by catalyzing the reduction of a wide range of cellular peroxides. Prxs have been identified in prokaryotes as well as in eukaryotes, however, the composition and number of Prxs family members vary in different species. In this study, six Prx s were firstly identified from the mud crab Scylla paramamosain by RT-PCR and RACE methods. Six Sp Prxs can be subdivided into three classes: (a) three typical 2-Cys enzymes denominated as Prx1/2, 3, 4, (b) two atypical 2-Cys enzymes known as Prx5-1 and Prx5-2, and (c) a 1-Cys isoform named Prx6. The evolutionarily conserved signatures of peroxiredoxin catalytic center were identified in all six Sp Prxs. Phylogenetic analysis revealed that Sp Prx3, Sp Prx4, Sp Prx5 s and Sp Prx6 were clearly classified into Prx3-6 subclasses, respectively. Although Sp Prx1/2 could not be grouped into any known Prx subclasses, Sp Prx1/2 clustered together with other arthropods Prx1 or unclassified Prx and could be classified into the typical 2-Cys class. The comparative and evolutionary analysis of the Prx gene family in invertebrates and vertebrates were also conducted for the first time. Tissue-specific expression analysis revealed that these six SpPrx s were expressed in different transcription patterns while the highest expression levels were almost all in the hepatopancreas. Quantitative RT-PCR analysis exhibited that the gene expression profiles of six SpPrx s were distinct when crabs suffered biotic and abiotic stresses including the exposures of Vibrio alginolyticus, poly (I:C), cadmium and hypoosmotic salinity, suggesting that the SpPrx s might play different roles in response to various stresses. The recombinant proteins including the Sp Prx1/2, Sp Prx4, Sp Prx5-1 and Sp Prx6 were purified and the peroxidase activity assays indicated that all these proteins can reduce H2 O2 in a typical DTT-dependent manner. To our knowledge, this is the first study about the comprehensive characterization of Prx gene family in Scylla paramamosain and even in crustaceans. These results would broaden the current knowledge of the whole Prx family as well as be helpful to understand and clarify the evolutionary pattern of Prx family in invertebrate and vertebrate taxa.